THE CHANGING URBAN ADMINISTRATIVE AUTHORITIES IN THE BEGINNING OF 19TH CENTURY - Ozguven, Yekta (YILDIZ TECHNICAL UNIV, 2011)
Through the period of Sultan Mahmud II, until 1826, the municipal administration of capital Istanbul has been performed by different authorities under the directorship of grandvizier (sadrazam). These authorities have been responsible from the security, cleaning and municipal police works in addition to public administration and architectural activities of the city. And also most of them were soldier members of the janissaries. With the abrogation of the janissaries, problems such as which urban works have been performed by which authority or association have been appeared. As a solution of these problems, new administrative units have been established and their responsibilities have been re-defined especially in 1830s.
Keywords: Istanbul; municipal administration; janissaries; public administration; Engineering